ANALISIS STUDI KELAYAKAN USAHA PENDIRIAN GENERAL TRADING AND SUPPLIER - Nuniek Dewi Pramanik; Intan Damarwati; Youda Subagja; Muhammad Ardly K F; Muhammad Ardly K F (JEBS (Journal of Economic and Business Student), 2022)
ABSTRACTThis study aims to determine the feasibility of business development carried out and the feasibility of investment by CV. Semesta Cahaya Rejeki from market and marketing aspects, legal aspects, hr and management aspects, amdal aspects, social economic aspects, and financial aspects. This company is a new business which was founded with its own capital, which is Rp. 500,000,000. The products produced are in the form of services that have a scope of work as a provider of industrial and office goods, such as Welding Equipment, Savety Equipment, Office Stationery, Mechanical, Electrical, and others. This study aims to determine the feasibility of CV.Semesta Cahaya Rejeki, the level of investment feasibility in the establishment of General Trading and Supplier CV. Semesta Cahaya Rejeki which is located at Jl. Edelweiss. Sukamukti Park Complex in Katapang,  Regency Bandung. The research was carried out in November-December 2021 with data collection techniques in the form of interviews, documentation and observation. The methods used are market and marketing aspects, technical aspects, organizational and management aspects, and financial aspects with the calculation of the feasibility of investment such as Payback Period (PP), Net Present Value (NPV), Internal Rate of Return (IRR), and Profitability Index (PI). The results of the analysis of each aspect showed positive results which stated that the business development carried out by CV. Semesta Cahaya Rejeki was feasible to operate and run.    ABSTRAKPenelitian ini bertujuan untuk mengetahi kelayakan pengembangan bisnis dan tingkat kelayakan investasi yang dilakukan oleh CV Semesta Cahaya Rejeki dari aspek legalitas dan hukum, aspek pemasaran, aspek sumber daya manusia dan manajemen, aspek AMDAL, aspek ekonomi sosial, dan aspek finansial. Perusahaan ini merupakan usaha baru yang didirikan dengan modal sendiri yaitu sebesar Rp. 500.000.000. Produk yang dihasilkan berupa jasa yang memiliki lingkup kerja sebagai penyedia barang kebutuhan industry dan kantor, seperti Welding Equipment, Savety Equipment, Alat Tulis Kantor, Mechanical, Electrical, dan lain-lain. CV. Semesta Cahaya Rejeki yang beralamat di Jl. Edelweis. Komplek Taman Sukamukti Katapang. Kab. Bandung. Penelitian dilaksanakan pada Bulan November – Desember 2021 dengan teknik pengumpulan data berupa wawancara, dokumentasi dan observasi. Metode yang digunakan yaitu aspek pasar dan pemasaran, aspek teknis, aspek organisasi dan manajemen, serta aspek finansial dengan perhitungan kelayakan investasi berupa Payback Period (PP), Net Present Value (NPV), Internal Rate of Return (IRR), dan Profitability Index (PI). Hasil analisis aspek masing-masing menunjukan hasil yang positif yang dinyatakan bahwa pengembangan Bisnis yang dilakukan oleh CV Semesta Cahaya Rejeki layak untuk beroperasi dan layak untuk dijalankan. Kata Kunci: Perdagangan Umum, Pengadaan, Studi Kelayakan, Aspek-aspek Studi Kelayakan Bisnis